The Effect Of Motivation And Compensation On Employee Performance Of Pt. Surabaya Wire - Peling; Mochamad Mochklas; Rina Maretasari (P3I UMSurabaya, 2025)
In companies, human resource management is an indispensable basis for efforts to develop and improve employee performance in order to achieve company goals. This research aims to determine the effect of motivation and compensation on the performance of PT employees. Surabaya Wire. This research method uses a quantitative approach. The data collection technique was carried out directly by distributing questionnaires to 60 respondents. Sample research using saturated sampling technique. The analysis tool uses SPSS software version 25. The research results show that (1) The motivation variable (X1) has a positive and significant effect on the performance of PT employees. Surabaya Wire, (2) The compensation variable (X2) has a positive and significant effect on the performance of PT employees. Surabaya Wire, (3) Motivation and compensation variables simultaneously have a positive and significant effect on the performance of PT employees. Surabaya Wire.